Aprendendo a aprender no universo médico - Silva, Jonatha Cajado Menezes e (2021)
INTRODUCTION: Undergraduate courses in medicine are going through an important period of transformation in the scientific training of medical professionals. The preparation of the student centered on the old concept of disease, easily found in dictionaries, as a biological change in the state of health, is outdated, understanding that patients have not only organic reasons for a medical appointment. Recognizing the need for reforms, researchers in medical education began a process of implementing a curricular structure where the focus would move away from teaching and migrate to learning. Called Active Teaching and Learning Methodologies are a set of educational strategies built on constructivism that position the student as a protagonist in the search for their knowledge, favoring self-directed and autonomous learning, METHODOLOGY: This is a systematic literature review with a qualitative approach. Literary research was carried out in PubMed, Web of Science, EMBASE and Virtual Health Library. The descriptors were selected by the Descriptors in Health Sciences/Medical Subject Headings and constructed by the PICO strategy. 736 articles were selected; articles from the last 5 years and in any language, which had medical students as a population, were included, in addition to the description of results observed in the acquisition of competences and/or skills through the MAEA. Secondary studies, texts that were not found in full and manuscripts with methodological errors were excluded. After applying the eligibility criteria, 39 articles from 18 different nationalities were included. RESULT AND DISCUSSION: Potentialities were observed in the acquisition of clinical skills through collaborative learning, that is, peers, with the construction of concepts through discussion among the students themselves, always led by a clinical Tutor, experienced in the method. The improvement of self-directed learning was also emphasized, ensuring that professionals learn to create a plan based on their observed needs, an autonomous study routine. The development of critical thinking skills was also highlighted, as the method depends on debate and interaction among students. Another key factor is experiential learning, introduced earlier today, providing the student with the acquisition of skills in real places of medical practice, or even through simulations, with standardized patient or high-tech mannequins. Teamwork ability was another skill exercised in learning environments now outside the traditional classroom benches. CONCLUSION: Discussions of assessments of the various teaching methods in medical education involve several criteria, and most are student perceptions. It is clear from the results presented in the following sections, the enormous potential that active learning has in acquiring skills that are essential for effective practice in the medical profession. A hybrid approach in methods, however, with an emphasis on active methodologies, would be an interesting scenario for students entering medical schools, allowing each strategy, combined with the student’s profile, to enhance individual knowledge gain.